DIGITAL TECHNOLOGY IN DEVELOPING THE FOUR ARABIC LANGGUAGE SKILLS - Rike Indah Veronika; Muhammad Afhon Ulin Nuha (Program Studi Pendidikan Bahasa Arab Fakultas Tarbiyah IAI Al-Qur'an Al-Ittifaqiah Indralaya, 2025)
This research aims to explore the utilization of digital technology in the Arabic language learning process. In the era of modern education, technology integration serves as a solution to address challenges related to resource efficiency and assessment objectivity. Utilizing a library research method, this article analyzes the role of digital devices and technology in supporting instructional quality. The study's findings indicate that the use of digital technology enables personalized learning, efficiency, long-term data management, and increased student enthusiasm. Evaluation is conducted through a comprehensive approach encompassing the stages of orientation, exploration, consolidation, and conclusion. This implementation is expected to significantly enhance the Arabic language competence of students in Indonesia.